Daily lighting integral levels on the quality of bell pepper seedlings under white led light (Bioagro, 2026)
This research evaluated the impact of different daily light integral (DLI) levels ranging from 8,6 to 22,68  mol·m⁻²·d⁻¹on the quality of bell pepper (Capsicum annuum L.) seedlings using white LED lighting. The study variables were leaf area index, root-to-shoot ratio, compactness, and quality index. A randomized 2x4 experimental design was used, evaluating two PPFD levels (200 and 350  µmol·m-2·s−1) and four photoperiods (12, 14, 16, and 18 h·d-¹). Eight treatments (DLI) with four replications were applied. The interaction between a PPFD of 200 µmol·m-2·s−1and a 14 h·d⁻¹ photoperiod resulted in a higher leaf area index, while root-to-shoot ratio, compactness, and seedling quality index were highlighted when 350 µmol m⁻²·s−¹ PPFD was combined with the 12 h·d⁻¹ photoperiod. These results are fundamental for controlled-environment agriculture, as they allow for the standardization of lighting protocols that ensure high-vigor seedlings for transplanting, while simultaneously promoting energy efficiency and reducing operational costs in vegetable production.
Keywords: DLI; interaction; light; pepper; photoperiod; seedling